2007
DOI: 10.1029/2007jd008709
|View full text |Cite
|
Sign up to set email alerts
|

Solar occultation satellite data and derived meteorological products: Sampling issues and comparisons with Aura Microwave Limb Sounder

Abstract: Derived Meteorological Products (DMPs, including potential temperature, potential vorticity (PV), equivalent latitude (EqL), horizontal winds and tropopause locations) from several meteorological analyses have been produced for the locations and times of measurements taken by several solar occultation instruments and the Aura Microwave Limb Sounder (MLS). MLS and solar occultation data are analyzed using DMPs to illustrate sampling issues that may affect interpretation and comparison of data sets with diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
222
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 176 publications
(237 citation statements)
references
References 109 publications
(151 reference statements)
15
222
0
Order By: Relevance
“…This corresponds to less than 10 % at the lower end of the profile and up to 15 % around 20 km. Velazco et al (2011) found similar differences in their comparisons of ACE-FTS and MkIV, which are based on noncoincident validation using a potential vorticity/potential temperature (PV/Theta) coordinate system (Manney et al, 2007). They also find largest deviations of the profiles around or slightly below 20 km, with maximum differences of up to ∼ 18 % and minimum differences of the order of ∼ 5 % around 17 km.…”
Section: Results Cfc-11: Mark IVmentioning
confidence: 76%
“…This corresponds to less than 10 % at the lower end of the profile and up to 15 % around 20 km. Velazco et al (2011) found similar differences in their comparisons of ACE-FTS and MkIV, which are based on noncoincident validation using a potential vorticity/potential temperature (PV/Theta) coordinate system (Manney et al, 2007). They also find largest deviations of the profiles around or slightly below 20 km, with maximum differences of up to ∼ 18 % and minimum differences of the order of ∼ 5 % around 17 km.…”
Section: Results Cfc-11: Mark IVmentioning
confidence: 76%
“…An sPV value of 1.4 × 10 −4 s −1 , or nearby values, have been used extensively in previous works (e.g. Manney et al, 1994aManney et al, , 2007Manney et al, , 2011Jin et al, 2006) to define the vortex edge centre. Values of 1.6 and 1.2 × 10 −4 s −1 have been used in the cited works to define the inner and outer edges, respectively, and the same values are used here.…”
Section: Coincidence Criteriamentioning
confidence: 99%
“…The location of a measurement with respect to the polar vortex was determined using scaled potential vorticity (sPV) values (Manney et al, 2007). For the ground-based instruments the values were calculated geometrically along the instrument's line of sight.…”
Section: Coincidence Criteriamentioning
confidence: 99%
“…enclosing the same area as a given PV contour); if the maximum gradient occurs at an equivalent latitude poleward of ±80 • , we consider the vortex to be undefined and set the maximum gradient equal to zero. To calculate the area of the polar vortex, we use the 1.4 × 10 −4 s −1 sPV contour as a simple proxy for the vortex edge (e.g., Manney et al, 2007). The total area of the vortex is then the area of the contour.…”
Section: Temperature and Vortex Diagnosticsmentioning
confidence: 99%